Efektivitas Pengelolaan Madrasah dalam Meningkatkan Mutu Pendidikan Islam di Madrasah Aliyah Swasta TPI Rambung Sialang - Suryanita Suryanita; Hadi Saputra Panggaebean; Manshuruddin Manshuruddin (Medan Resource Center, 2026)
This study aims to analyze the effectiveness of madrasah management in improving the quality of Islamic education at Madrasah Aliyah Swasta TPI Rambung Sialang. Previous studies mostly examined educational quality and madrasah management separately, while limited research has explored how integrated management practices directly contribute to improving Islamic education quality. This gap underlines the importance of examining effective management indicators in madrasah institutions. This study employed a qualitative approach using purposive and snowball sampling techniques. Informants included the head of the madrasah, teachers, committee members, and students. Data were collected through interviews, observations, and documentation studies, then analyzed through data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation techniques. The indicators of management effectiveness included transformational leadership, school-based management, teacher commitment, stakeholder collaboration, and competency-oriented learning supervision. The findings show that effective madrasah management is reflected in strong leadership, active collaboration with parents and the community, and continuous monitoring of student development. These practices contributed significantly to improving students’ academic and religious competencies. The novelty of this study lies in integrating leadership, collaboration, and competency-based management as key determinants of Islamic education quality improvement. Practically, the findings provide guidance for developing participatory and quality-oriented madrasah management systems.